The role of logical-sociological methods in applied research in higher education pedagogy - Peredelskiy, A.A.; Mamedov, Azer Agabala ogly; Kortunov, V.V.; Zaitsev, A.A. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to determine the prospects for applying logical-sociological methods and operations in specialised applied pedagogical scientific and qualification research in the field of physical culture and sport based on meta-scientific analysis. Methods and structure of the study. A meta-scientific analysis of the prospects for applying logical-sociological methods and operations in specialised applied pedagogical scientific and qualification research in the field of physical culture and sport has been carried out. Results and conclusions. The interdisciplinary nature of pedagogical knowledge confirms the possibility and expediency of integrating pedagogical and specific sociological research, demonstrating a model of synthesis between pedagogy and sociology using the example of preparing and defending scientific qualification works on pedagogy. The formation of a meta-scientific algorithm for a promising solution to a pedagogical problem makes it possible to overcome the subject uncertainty of the basic and applied disciplines of the social sciences and humanities.